35 Use of mass transfusion scales in prehospital setting. (26th April 2019) - Bélanger-Quintana, D; de la Cuerda del Olmo, J; Sanz de Miguel, E; Corral Torres, E; Apilluelo Gutierrez, S; Castellanos Muñoz, M; Ramirez Freire, L; Zubillaga Carmona, LL; Bernardino Cuesta, B
Abstract : Background: Hemorrhagic shock is one of the leading causes of death in trauma. Prompt implementation of transfusion with blood related products and surgery mitigate the effects of bleeding and shock. Early warning of mass transfusion needs by prehospital units could shorten the time of initiation of hospital protocols. Objective: To evaluate the adequacy of mass transfusion scales TASH and ABC in the prehospital setting. Method: Case control study of patients that were transfused in hospital and were treated and transported by SAMUR - Civil Protection. Both TASH and ABC scales were calculated and related with who received transfusion. Statistical analysis was used to describe the relation. Results: A total of 66 patients received transfusion. Median age of 41.5 years. 74.2% were male. A cut-off point of 16 or more was used as positive for transfusion need in the TASH scale and of 2 or more for the ABC scale. TASH showed a 100% sensitivity for transfusion need and ABC showed a 67%. Conclusion: Using predictive scales in the prehospital setting could give hospitals more time to activate their mass transfusion protocols. Scales should be easy to use and calculate. TASH has shown to be a good scale but is harder to calculate than ABC. Further testing of other scales could prove helpful to better the warning system between hospital and prehospital units. References: Massive transfusion predictive scores in trauma. Experience of a transfusion registry M. Chico-Fernández, C. García-Fuentes, M.A. Alonso-Fernández, D. Toral-Vázquez, S. Bermejo-Aznarez, E. Alted-López. Trauma Associated Severe Hemorrhage (TASH)-Score: Probability of Mass Transfusion as Surrogate for Life Threatening Hemorrhage after Multiple Trauma Yücel, Nedim MD; Lefering, Rolf PhD; Maegele, Marc MD; Vorweg, Matthias MD; Tjardes, Thorsten MD; Ruchholtz, Steffen MD; Neugebauer, Edmund A. M. PhD; Wappler, Frank MD; Bouillon, Bertil MD; Rixen, Dieter MD; the 'Polytrauma Study Group of the German Trauma Society'. Early prediction of massive transfusion in trauma: simple as ABC (assessment of blood consumption)? Nunez TC1, Voskresensky IV, Dossett LA, Shinall R, Dutton WD, Cotton BA. Conflict of interest: None. Funding: None.